THE USE OF MIND MAPPING BOARD (MMB) TO IMPROVE SPEAKING ABILITY IN FACING INDUSTRIAL REVOLUTION 4.0 - Olyvia Revalita Candraloka; Aliva Rosdiana (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2022)
This study aims at seeing the effect of students’ ability in speaking using Mind Mapping Board (MMB).  There are 30 students who consists of 14 female and 16 male students at seven grade of one of Junior High School Kudus. The data collection is collected by interview, observation, questionnaire, and test. The research design used was Quasi Expreriment. It is used to know the effectiveness of MMB using two treatments, namely pre-treatment and post-treatment. By mind mapping, the ideas will be elaborated well and organized into framework of mapping. MMB is a media used to help students to extend their creative ideas and help them to be able to communicate. Communication skill plays an important role in supporting the 4.0 industrial revolution. Finally, MMB media is an effective way for students to organize concepts and ideas to support their speaking skills and prepare communication skills in the era of industrial revolution 4.0.